PERSEPSI MASYARAKAT HURABA TERHADAP PINJAMAN PEMBIAYAAN OLEH BTPN SYARIAH DALAM PENINGKATAN USAHA DITINJAU DARI HUKUM ISLAM - Siti Kholijah; Pitriani Gultom (EKSYA : Jurnal Ekonomi Syariah, 2022)
BTPN Syariah is a financial institution whose main business is to provide credit and other services in payment traffic and money circulation, and operates according to sharia principles. In addition to these main businesses, BTPN Syariah also provides business capital financing loan programs to the public. The business capital financing loan is intended to empower the community, especially women so that their welfare increases. One of the communities empowered by the BTPN Syariah financing program is the Huraba I Village community, Kec. Siabu Kab. Christmas Mandailing. This study uses a qualitative method with a descriptive analytical approach. Methods of collecting data obtained through direct observation, interviews and documentation. The data analysis technique was carried out by means of data reduction, the last data display was concluded. The subjects in this study were the people of Huraba I Village, Kec. Siabu Kab. Mandailing Natal and or BTPN Syariah bank customers and BTPN Syariah parties. The results of the study concluded that the practice of accounts payable with both parties benefited from each other, namely Muqtarid (the borrower) getting a loan so that he could meet his needs. Meanwhile, Muqrid (who provides loans) also gets what he is entitled to, namely profits from the results of his sacrifices and the reason behind the practice of debt is because of the convenience in covering the needs of the local community and the process is easy, fast and does not have to leave collateral. According to Islamic law, financing loans provided by BTPN Syariah in business development contain elements of usury because the principle between the borrower and the BTPN Syariah bank uses the interest principle and depends on the interest system applied to conventional banks. Therefore, any addition to the loan amount from the debtor is said to be usury, but it depends more on the background and the consequences. As with the additions contained in the debt transactions that occurred in Huraba I Village, Kec. Siabu Kab. The additional Mandailing Natal in the debt transaction is an addition that can be taken because the average loan is for business capital and with this addition it does not cause a downturn in economic life.